Nutritious subsistence food systems - Graham, RD; Welch, R.M.; Saunders, DA; Ortíz Monasterio, Jose Iván; Bouis, Howarth E.; Bonierbale, Merideth W.; Haan, Stef de; Burgos, G.; Thiele, Graham; Liria Domínguez, M.R.; Meisner, CA; Beebe, Stephen E.; et al. (2007)
The major subsistence food systems of the world that feed resource?poor populations are identified and their capacity to supply essential nutrients in reasonable balance to the people dependent on them has been considered for some of these with a view to overcoming their nutrient limitations in sound agronomic and sustainable ways. The approach discusses possible cropping system improvements and alternatives in terms of crop combinations, external mineral supply, additional crops, and the potential for breeding staples in order to enhance their nutritional balance while maintaining or improving the sustainability and dietary, agronomic, and societal acceptability of the system. The conceptual framework calls for attention first to balancing crop nutrition that in nearly every case will also increase crop productivity, allowing sufficient staple to be produced on less land so that the remaining land can be devoted to more nutrient?dense and nutrient?balancing crops. Once this is achieved, the additional requirements of humans and animals (vitamins, selenium, and iodine) can be addressed. Case studies illustrate principles and strategies. This chapter is a proposal to widen the range of tools and strategies that could be adopted in the HarvestPlus Challenge Program to achieve its goals of eliminating micronutrient deficiencies in the food systems of resource?poor countries.